The Availability of Blue Swimming Crab (Portunus pelagicus, Linnaeus, 1758) in seaweed culture area of marine coastal waters. Issue 1 (September 2020) - Musbir; Sudirman; Bohari, Ridwan
Abstract: Seaweed cultures in marine coastal waters provide providing microhabitats, shelter, and food sources to fish and invertebrate. The availability of blue swimming crab ( Portunus pelagicus ) in seaweed culture area was conducted from October to December 2019 in the south coastal waters of Bulukumba Regency, South Sulawesi, Indonesia. The purpose of the study was to assess the catch, size, and sex distribution of the blue swimming crab in the area. The crabs were caught by set bottom gillnets with 4 inches of mesh sizes and 300 m of a length. The carapace width (CW) and sex for each crab individual were recorded. The results of the study show that the total catch of 21 trips during 3-month fishing operation was 539 crabs that consist of 260 male (48.24 %) and 279 females (51.76 %). The (CW) of males ranged from 53.6 to 143.6 mm, while females ranged from 58.3 to 142.8 mm. There were 38 breeding crabs or 13.62 % from the female total. The carapace width of breeding crab ranged from 92.2 to 138.6 mm. Moreover, it needed to study in the area intensively.